Επίπεδα ενσυναίσθησης και ηθική κρίση στους επαγγελματίες υγείας - Μερτίκα, Ελένη (Πανεπιστήμιο Πελοποννήσου, 2022)
Introduction: Patient understanding is what makes empathy important in health care, providing all the benefits of increased therapeutic distinction and compliance. This ability can be innate or acquired and is a precursor to moral judgment and moral perception of care that each health professional forms. Aim: Investigation of empathic capability and moral judgment in the nursing staff of the General Hospital of Corinthos. In particular, the study of the relationship between the empathy and the moral composition of the nursing staff is sought, in order to determine the degree of its interaction in formatting the personality and behavior of health professionals in relation to the patient. In addition, the effect of demographic characteristics on the levels of empathy and moral values of nurses is examined. Evidence-Method: A cross-sectional descriptive correlation study was conducted with a sample of convenience and the use of structured questionnaires. The sample of the research consisted of 150 nurses working at the General Hospital of Corinthos. Empathy was assessed with the Interpersonal Reactivity Index (IRI) questionnaire, while moral judgment was assessed with the Moral Competence Test (MCT). SPSS 22.0 was used for the statistical analysis. Results: Health professionals scored higher than average on cognitive empathy and empathic concern, with cognitive empathy ahead of all. Fantasy empathy and personal distress were lower than average, with fantasy empathy recording the lowest values. Age, marital status and work experience were directly related to cognitive processes. In the emotional subscales, there was a correlation between empathic concern and not having a master's degree and a correlation between marital status, not having a master's degree and professional experience with personal distress. In the assessment of ethical competence, the C index recorded a low value, with the majority of participants (62.7%) noting a very low level of moral judgment. In the results of the analysis, the C index is influenced by the level of education, the level of postgraduate studies and the professional experience. No correlation was observed between the four scales of interpersonal response and moral judgment capacity. Conclusions: The study population of hospital nursing personnel showed a capacity for empathy that promotes altruistic behaviors, and low Imoral judgment. Empathy and moral judgment are the cornerstone of providing ethical care. Both are variable capabilities that can be taught, providing a dual benefit, both to ensure quality care and to maintain the mental health of health care personnel. Key words: empathy, moral judgment, healthcare empathy, care ethics, health professionals.
Αριθμός Εισαγωγής: 013430 cd
Keywords: Ενσυναίσθηση -- Περιπτωσιολογικές μελέτες; Ηθική -- Περιπτωσιολογικές μελέτες; Υπηρεσίες υγείας -- Ελλάδα -- Περιπτωσιολογικές μελέτες; Υγειονομικό προσωπικό -- Ελλάδα -- Περιπτωσιολογικές μελέτες; Νοσηλευτική ηθική -- Περιπτωσιολογικές μελέτες; Ενσυναίσθηση; Ηθική κρίση; Ενσυναίσθηση της φροντίδας υγείας; Ηθική της φροντίδας υγείας; Επαγγελματίες υγείας; Empathy; Moral judgement; Healthcare empathy; Care ethics; Health professionals